PROSPECTS FOR INNOVATIVE DEVELOPMENT OF THE AGRICULTURAL SECTOR OF THE ECONOMY IN THE CONDITIONS OF WAR AND GLOBAL CHALLENGES - ZHAIVORON, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the current state and prospects of innovative development of Ukraine’s agricultural sector under the conditions of war and global challenges. It is established that until 2022 the sector was one of the key drivers of the national economy, accounting for about 10–12% of GDP and over 40% of the country’s foreign exchange earnings, while Ukraine ranked among the world’s top three exporters of grain and sunflower oil. It is proven that the full-scale invasion has led to significant losses: reduction of cultivated areas, decline in grain and oilseed production, destruction of machinery, elevators, and irrigation systems, land contamination with mines, as well as disruption of logistics due to port blockades and interruptions in resource supply. The impact of climate change, rising production costs, and resource shortages on the stability of agricultural output is outlined. It is determined that additional risks include soil degradation, water scarcity, and the spread of extreme weather events. The potential of innovative technologies – precision agriculture, smart farming, digital platforms, drones, satellite monitoring, the Internet of Things, biotechnology, vertical farms, and eco-oriented solutions – in improving the efficiency and resilience of agricultural production is explored. The importance of digitalization, automation, and biotechnology in reducing production risks and adapting to climate change is emphasized. The key barriers to innovative development are analyzed: financial (limited access to credit, high cost of technologies), human resources (shortage of specialists, outflow of young professionals), security (landmines, destroyed infrastructure), and regulatory (lack of legal framework for new technologies). The proposed solutions include the development of state and international support programs, attraction of investments, improvement of educational training, and adaptation of legislation to the needs of agro-innovation. It is shown that the integration of Ukraine’s agricultural sector into the European agricultural space is possible through participation in EU programs, access to structural funds, harmonization of standards, and implementation of the Green Deal environmental requirements. It is concluded that the innovative development model is a necessary condition for maintaining competitiveness, increasing efficiency and resilience of agricultural production, as well as strengthening Ukraine’s role in ensuring global food security.
Keywords: agricultural sector of Ukraine; innovative development; precision farming; smart farming; digitalization; drones; biotechnology; eco-oriented technologies